Sosialisasi Aplikasi Si Apik bagi Pelaku Industri Kecil Menengah Kabupaten Magetan - Mohammad Sofyan; Iin Andrayanti; Anwar Atmojo (Gapenas Publisher, 2022)
Preparing financial statements is important for Small and Medium Industries to maintain cash flow and not mix between personal and business finances, as well as monitor business development. They are preparing financial statements that we commonly encounter are still widely used hardware such as computers and laptops. Bank Indonesia, in collaboration with the Indonesian Accounting Association, has issued an application for preparing financial statements following SAK EMKM, namely the SI APIK. The SI APIK can be accessed through computers, laptops, and smartphones. SI APIK aims to make it easier for business actors, especially MSMEs, to compile financial statements. Small and Medium Industries members of the Magetan Regency Promotion House prepare financial reports manually / conventionally. This Community Service activity aims to introduce the SI APIK to Small and Medium Industries, starting from downloading and using the application, registering a business through the application, and introducing the features of the SI APIK and how to read the output. The results of this activity are expected to help Small and Medium industries manage finances and prepare financial reports properly and correctly per SAK EMKM